(untitled) (American Journal of Aquaculture and Animal Science, 2025)
This study assesses the nutritional value and practical viability of Yeheb (Cordeauxia edulis) foliage as a prominent camel feed during dry seasons in Bokh Woreda, Dollo Zone, Ethiopia. Yeheib is an indigenous drought-resistant shrub tree that plays an important role in pastoralist communities, although its nutritional value and effect on camel feed remain un researched so far. A mixed research methods approach consisting of Household surveys, Field observations, and laboratory analysis was used to evaluate the Nutritional composition, availability, and utilization of Yeheb foliage. Findings indicated that Yeheb is widely recognized as an essential forage, with 91% of respondents regularly using it as camel feed, particularly during the dry season. Laboratory analysis showed that Yeheb contains moderate crude protein (9.6%), high dry matter (94.92%), and significant fiber content, making it a viable supplement for sustaining camel health and productivity. Furthermore, pastoralists described benefits such as increased body condition, weight gain, enhanced milk production, and boosted drought resilience among camels consuming Yeheb. Nevertheless, challenges such as overgrazing, excessive cutting, and limited awareness hinder its optimum utilization. To increase its widely use, the research recommends increasing awareness among pastoralists, implementing conservation approaches, and encouraging the cultivation of Yeheb to ensure future availability. Strengthening local knowledge and management practices could help integrate Yeheb into sustainable camel feeding systems, thereby improving pastoral resilience in the study area.